The Role of Pesantren in Maintaining National Resilience in the Modern Era - Fauzi Majid, Nurazmi; Nurwahidin, Nurwahidin (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This article explores how pesantren, as a traditional Indonesian Islamic educational institution, plays a significant role in safeguarding the nation's resilience amidst the challenges brought by modernization and globalization. The study employs a qualitative method, utilizing literature review as the data collection technique, and presents its findings through descriptive analysis. The research reveals that pesantren contributes to national resilience by nurturing spiritual values, discipline, and character development in santri, which equips them to address complex modern issues. It emphasizes the relevance of pesantren in preserving cultural and social values while adapting to technological advancements. The paper concludes that pesantren remains a crucial institution for maintaining national stability by promoting education, societal cooperation, and economic empowerment within local communities. The implications of these findings suggest that pesantren's unique educational approach continues to offer valuable strategies for navigating modern societal challenges.